Strategi bisnis, leverage keuangan dan kinerja perusahaan - Krismiaji Krismiaji (Jurnal Akuntansi dan Auditing Indonesia, 2017)
This paper is an empirical research investigating the impact of business strategy toward causality relationship between corporate leverage and its financial performance. Sample used in this study are 645 manufacture company listed in Indonesia Stock Exchange (IDX) during period of 2010 â€“ 2014. Companyâ€™s performance is measured by Market to Book Value ratio, leverage is measured by dividing total debt to total assets, and competitive strategy is measured by dummy variable, where 1 is for company adopted product differentiation strategy and 0 is for those adopted cost leadership strategy. This research found negative impact of leverage toward financial performance and the impact is more severe for company adopted product differentiation strategy. The result of this research is expected to help explaining why the previous studies investigated direct relationship between leverage and performance tend to be not consistent and contradictive.Â